2020
DOI: 10.1007/s00420-020-01539-0
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer risks of firefighters: a systematic review and meta-analysis of secular trends and region-specific differences

Abstract: Purpose The objective of this study was to conduct a systematic review and meta-analysis to evaluate the cancer risks among firefighters in the time course and from different geographical areas. Method A PubMed search was performed to identify cohort studies about cancer risk and firefighting presented with standardized incidence ratios (SIRs) or standardized mortality ratios (SMRs). Using random-effect models, meta-relative risk estimates (mSIRs, mSMRs) and 95% confidence intervals (CI) were assessed. Cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 61 publications
18
41
0
3
Order By: Relevance
“…The WTC combined Rescue/Recovery cohort includes firefighters, law enforcement and construction workers. An increased risk of melanoma has consistently been reported in previous studies of firefighters (Casjens et al, 2020) and police officers (Finkelstein, 1998, Forastiere et al, 1994, Harris et al, 2018, while results of studies of construction workers are mainly negative (Alicandro et al, 2020, Gallagher et al, 1987, Hakansson et al, 2001, Robinson et al, 1995. Workplace exposure to UV radiation has been suggested to explain these findings, since other occupational groups with opportunity of UV exposure, such as offshore workers (Stenehjem et al, 2017), airline pilots and cabin crews (Sanlorenzo et al, 2015), and agricultural workers (Kachuri et al, 2017) also experience an increased incidence of melanoma.…”
mentioning
confidence: 81%
“…The WTC combined Rescue/Recovery cohort includes firefighters, law enforcement and construction workers. An increased risk of melanoma has consistently been reported in previous studies of firefighters (Casjens et al, 2020) and police officers (Finkelstein, 1998, Forastiere et al, 1994, Harris et al, 2018, while results of studies of construction workers are mainly negative (Alicandro et al, 2020, Gallagher et al, 1987, Hakansson et al, 2001, Robinson et al, 1995. Workplace exposure to UV radiation has been suggested to explain these findings, since other occupational groups with opportunity of UV exposure, such as offshore workers (Stenehjem et al, 2017), airline pilots and cabin crews (Sanlorenzo et al, 2015), and agricultural workers (Kachuri et al, 2017) also experience an increased incidence of melanoma.…”
mentioning
confidence: 81%
“…As mentioned above, an ingestion of Sb by humans can cause a variety of disorders, such as irritation of the eyes, severe vomiting, diarrhea, skin lesions, lung diseases, heart problems, stomach ulcers [67,70] and different types of cancers, including PCa [31][32][33][34]. In spite of a significant correlations between Sb exposure and the risk of PCa have been There are some limitations in our study, which need to be taken into consideration when interpreting the results of this review.…”
Section: All Natural Chemical Elements Of the Periodicmentioning
confidence: 99%
“…Furthermore, experimental and epidemiological data identified that Sb compounds should be considered as genotoxic carcinogens [30][31][32][33][34]. Consequently, the International Agency for Research on Cancer (IARC) has evaluated Sb as possibly carcinogenic to humans (Group 2B) [35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations